Alterations in the Antioxidant Enzyme Activities in the Neurodevelopmental Rat Model of Schizophrenia Induced by Glutathione Deficiency during Early Postnatal Life - Magdalena Górny; Anna Bilska-Wilkosz; Małgorzata Iciek; Marta Hereta; Kinga Kamińska; Adrianna Kamińska; Grażyna Chwatko; Zofia Rogóż; Elżbieta Lorenc-Koci (MDPI AG, 2020)
The aim of the present study was to assess the effects of l-buthionine-(S,R)-sulfoximine (BSO), a glutathione (GSH) synthesis inhibitor, and GBR 12909, a dopamine reuptake inhibitor, administered alone or in combination to Sprague-Dawley rats during early postnatal development (p5-p16), on the levels of reactive oxygen species (ROS), lipid peroxidation (LP) and the activities of antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione disulfide reductase (GR) in peripheral tissues (liver, kidney) and selected brain structures (prefrontal cortex, PFC; hippocampus, HIP; and striatum, STR) of 16-day-old rats. The studied parameters were analyzed with reference to the content of GSH and sulfur amino acids, methionine (Met) and cysteine (Cys) described in our previous study. This analysis showed that treatment with a BSO + GBR 12909 combination caused significant decreases in the lipid peroxidation levels in the PFC and HIP, in spite of there being no changes in ROS. The reduction of lipid peroxidation indicates a weakening of the oxidative power of the cells, and a shift in balance in favor of reducing processes. Such changes in cellular redox signaling in the PFC and HIP during early postnatal development may result in functional changes in adulthood.